Antenatal screening for Down syndrome: A quantitative demonstration of the improvements over the past 20 years. (October 2013) - Renshaw, Richard; Ellis, Katrina; Jacobs, Patricia; Morris, Joan
Objectives: Pregnant women who receive a high screening risk result for Down, Edwards or Patau syndrome are offered diagnostic tests that carry a procedure-related risk of miscarriage. This study quantifies the improvement in the screening tests by calculating the number of women who had such tests per syndrome diagnosis from 1991 to 2010. Methods: Routinely stored data on prenatal chorionic villus sampling (CVS) and amniocentesis samples performed from 1991 to 2010 from the Wessex Regional Genetics Laboratory in England were extracted from the laboratory database. The numbers of diagnostic tests performed per Down, Edwards or Patau syndrome diagnosis were calculated according to the type of diagnostic test, and were adjusted for maternal age and gestational age at diagnosis. Results: A total of 32, 345 CVSs and amniocenteses identified 872 diagnoses of Down syndrome and 328 of Edwards and Patau syndrome. In 1991, there were 46 (95%CI: 16–111) CVSs per syndrome diagnosis compared with five (95%CI: 4–7) in 2010. For amniocenteses, the number fell from 53 (37–78) to 15 (11–22). Conclusion: This analysis demonstrates the improvements in antenatal screening for Down syndrome that have been made over the past 20 years, resulting in a reduction in the number of women tested and thus in the number of foetal deaths attributable to the testing procedure.